Ionotropic gelation fronts in sodium carboxymethyl cellulose for hydrogel particle formation - Sharratt,WN; Lopez,CG; Sarkis,M; Tyagi,G; O'Connell,R; Rogers,SE; Cabral,JT (Gels, 2021)
Hydrogel microparticles (HMPs) find numerous practical applications, ranging from drug delivery to tissue engineering. Designing HMPs from the molecular to macroscopic scales is required to exploit their full potential as functional materials. Here, we explore the gelation of sodium carboxymethyl cellulose (NaCMC), a model anionic polyelectrolyte, with Fe3+ cations in water. Gelation front kinetics are first established using 1D microfluidic experiments, and effective diffusive coefficients are found to increase with Fe3+ concentration and decrease with NaCMC concentrations. We use Fourier Transform Infrared Spectroscopy (FTIR) to elucidate the Fe3+-NaCMC gelation mechanism and small angle neutron scattering (SANS) to spatio-temporally resolve the solution-to-network structure during front propagation. We find that the polyelectrolyte chain cross-section remains largely unperturbed by gelation and identify three hierarchical structural features at larger length scales. Equipped with the understanding of gelation mechanism and kinetics, using microfluidics, we illustrate the fabrication of range of HMP particles with prescribed morphologies